The Low Keratin Affinity of Efinaconazole Contributes to Its Nail Penetration and Fungicidal Activity in Topical Onychomycosis Treatment - Sugiura, Keita (American Society for Microbiology, 2014)
Onychomycosis is a common fungal nail disease that is difficult to treat topically due to the deep location of the infection under the densely keratinized nail plate. Keratin affinity of topical drugs is an important physicochemical property impacting therapeutic efficacy. To be effective, topical drugs must penetrate the nail bed and retain their antifungal activity within the nail matrix, both of which are adversely affected by keratin binding. We investigated these properties for efinaconazole, a new topical antifungal for onychomycosis, compared with those of the existing topical drugs ciclopirox and amorolfine. The efinaconazole free-drug concentration in keratin suspensions was 14.3%, significantly higher than the concentrations of ciclopirox and amorolfine, which were 0.7% and 1.9%, respectively (P < 0.001). Efinaconazole was released from keratin at a higher proportion than in the reference drugs, with about half of the remaining keratin-bound efinaconazole removed after washing. In single-dose in vitro studies, efinaconazole penetrated full-thickness human nails into the receptor phase and also inhibited the growth of Trichophyton rubrum under the nail. In the presence of keratin, efinaconazole exhibited fungicidal activity against Trichophyton mentagrophytes comparable to that of amorolfine and superior to that of ciclopirox. In a guinea pig onychomycosis model with T. mentagrophytes infection, an efinaconazole solution significantly decreased nail fungal burden compared to that of ciclopirox and amorolfine lacquers (P < 0.01). These results suggest that the high nail permeability of efinaconazole and its potent fungicidal activity in the presence of keratin are related to its low keratin affinity, which may contribute to its efficacy in onychomycosis.